Ectoparasitic infestation of the Nile Squeaker, Synodontis schall (Bloch and Schneider, 1801) from the Cross River Estuary, Nigeria - Eyo, Victor Oscar; Effanga, Emmanuel Offiong (International Journal of Aquatic Biology, Iranian Society of Ichthyology, 2018)
The objective of this study was to determine the abundance, intensity and prevalence of ectoparasites of Synodontis schall from the Cross River Estuary, Nigeria. A total of 150 fresh samples were collected between May and October, 2013 from the catches of the artisanal fisheries at Nsidung beach. The skin, gill and fin scrapping were prepared from each specimen and examined following standard methods for microscopic analysis. The results showed that 21 specimens were infested with 77 ectoparasites belonging to five species, including Trichodina sp., protozoan cyst, Ergasilius lizae, Dactylogyrus sp. and Gyrodactylus sp. with an overall prevalence of 14.0%. Infestation rate was highest in 10-14.9 cm class size (53.55%), followed by 15-19.9 cm (34.00%), ≥20.0 cm (8.00%) and 5-9.9 cm (4.67%) size classes. Parasites were more prevalent in the gills (82%), followed by the skin (14%) and least (4%) in the dorsal fin. Prevalence and abundance of ectoparasites was highest (28.57% and 0.71) in 5-9.9 cm size class, followed by 10-14.9 cm (16.25% and 0.60), 15-19.9 cm (9.80% and 0.41) and ≥20.0 cm (8.33% and 0.25) classes. Prevalence and abundance of ectoparasites was higher in female (15.63% and 0.56) than male (11.11% and 0.43). Dactylogyrus sp., Trichodina sp., protozoan cyst and E. lizae exhibited organ specificity as they were specifically recovered from the gills whereas Gyrodactylus sp. was found in the skin and fin. However, it was concluded that to prevent zoonosis, S. schall should be washed with clean water and cooked properly before consumption.
Keywords: Ectoparasitic infestation; Abundance; Intensity; Prevalence